Global Vaccine Action Plan Lessons Learned II: Stakeholder Perspectives. Issue 33 (14th July 2020) - Hwang, Angela; Veira, Chantal; Malvolti, Stefano; Cherian, Thomas; MacDonald, Noni; Steffen, Christoph; Jones, Ian; Hinman, Alan; Mantel, Carsten
Highlights: GVAP built visibility for immunization and was an improvement over prior plans. GVAP implementation was incomplete due to limited awareness and stakeholder buy-in. The GVAP Monitoring & Evaluation/Accountability framework gave valuable guidance. Future strategies should build greater buy-in and communicate more effectively. Abstract: Introduction: The Global Vaccine Action Plan (GVAP), unanimously endorsed by the World Health Assembly in 2012, defined an ambitious strategy to improve immunization. At the end of the decade, significant progress has been made but four of the five GVAP goals are likely to be missed. This report describes a set of surveys and interviews relating to GVAP, conducted to inform the immunization strategy for the next decade. Methods: Three surveys and two sets of semi-structured interviews were conducted from 2017 to 2019. Respondents consisted of immunization stakeholders at global, regional, and country levels, and included individuals who had been involved in the development and implementation of GVAP or its monitoring, evaluation and accountability (M&E/A) process; national immunization managers; academics; and personnel from non-governmental organizations and civil society organizations. Results: The surveys and interviews gave consistent results. They highlighted the value of GVAP in increasing visibility for immunization and the benefits of the GVAP M&E/A framework. The main limitations of GVAP were identified as the limited ownership by countries and other stakeholders leading to incomplete implementation of the strategy and poor accountability for achieving GVAP targets. Discussion: These results informed the review of GVAP and the development of its successor strategy, the Immunization Agenda 2030. In addition, these surveys and interviews identified two challenges in assessing the value of GVAP: the need to rely exclusively on stakeholder perspectives and difficulties in attributing benefits. These challenges are inherent in evaluating an over-arching strategy such as GVAP and should be factored into interpretation of the results.